Konstruksi Realitas Sosial Tafsir Al-Qur’an pada Unggahan @peachyfraise dalam Media Sosial X - Nugroho, Ihsan; Efendi, Erwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
Al-Qur’an is a text that teaches equality and justice between men and women, but the interpretations made by clerics and scholars throughout history are often considered to be influenced by their social and cultural context, which can create gender bias. This bias can occur in various aspects of life, including in the workplace, education, media, and everyday social interactions. In a media context, there was an interesting upload made by the @peachyfraise account on social media X which then received a debate response. This research aims to identify the social construction that occurs in one of the posts about the interpretation of the Al-Qur'an. This research uses a qualitative methodology by applying the social construction theory proposed by Peter L. Berger and Thomas Luchkmann. The findings of this research focus on how ready and able individuals are to face the modern world, where they must be able to make decisions regarding their attitudes based on their skills and abilities.